The hospital provision of reasonable adjustments for people with learning disabilities: Findings from Freedom of Information requests. (16th August 2018) - Heslop, Pauline; Read, Stuart; Dunwoodie Stirton, Fred
Accessible Summary: The Equality Act2010 is a law to make sure that people are treated fairly. The law says that anyone providing a service to the general public, including hospitals, must make "reasonable adjustments" for disabled people. A reasonable adjustment is changing the way the hospital usually does things so that disabled people are able to use their services. The aim of this study was to find out whether the funders of health care (called Clinical Commissioning Groups or CCGs) and hospitals were keeping to the Equality Act2010 . Some funders and hospitals did not reply to our questions. All of the other funders said that they wrote into their agreements that disabled people must be able to use the hospital. Eight of 186 told us that they checked up on whether this happened or not. Most of the hospitals could tell us the number of people with learning disabilities that had been inpatients, but fewer could tell us the number of people with learning disabilities who used outpatients or accident and emergency. About half of the hospitals said they did not check up on services for people with learning disabilities or they did not share these reports with the public. This research is important because it suggests that some hospitals may not be following the Equality Act2010, and that more could be done to make sure that people with learning disabilities are able to access health care. Abstract: Background: The Equality Act2010 places a duty on service providers to make "reasonable adjustments" for disabled people. The aim of this study was to explore key aspects relating to the provision of reasonable adjustments for people with learning disabilities in hospitals. Methods: The research questions were explored using Freedom of Information (FOI) requests submitted to 206 CCGs and 141 hospital trusts in England. Results: One hundred and eighty‐six CCGs reported that they included the requirement to provide equal access to services in their contracts with providers. Eight CCGs provided evidence about how they ensured reasonable adjustments were provided. One hundred and twelve of 132 responding hospital trusts provided information about the number of inpatients with learning disabilities; eighty‐three of 132 provided data about outpatients and 88 of 132 provided data about A&E. Sixty‐four of 125 responding trusts explicitly stated that they did not undertake audits of learning disability services or did not make any such reports publicly accessible. Conclusions: The findings contribute to concern about the gap between legislation and guidance, and its practical application "on the ground." If CCGs are not assessing contractual compliance to provide equitable access to services for people with learning disabilities, and trusts are not aware of the number of people with learning disabilities using their services, or their access requirements, this raises concerns about their compliance with the Equality Act2010 .